Work autonomy, work pressure and job satisfaction: an analysis of EU countries - Lopes, H.; Lagoa, S.; Calapez, T. (Economic and Labour Relations Review, 2014)
Based on European Working Conditions Survey (EWCS) micro-data, we show that, on average, work autonomy has declined and work pressure has increased in most European Union countries since 1995. Since such evolution is substantially detrimental for workers, we examine whether workers of varied skill levels in different countries have been equally impacted. Descriptive analysis shows that low-skill clerical workers are the most affected and that Scandinavian countries fare better. Econometric results show that the decline in job satisfaction is due mainly to the increase in work pressure—which might be reaching a limit for high-skill workers—and that job satisfaction is most affected by an increase in work pressure when this is not accompanied by greater work autonomy.